Effect Of Management Control System On Employee Performance (Case Study of PT. Charoen Pokphand Indonesia) - Rahayu Anis Khikmawati; Budi Utomo (JEBDEKER: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital, Ekonomi Kreatif, Entrepreneur, 2021)
The aim of this research is analyze the effect of management control systems on employee performance at PT. Charoen Pokphand Indonesia. This type of research is quantitative research and the data source is primary data with a questionnaire. The sample in this study were employees at PT. Charoen Pokphand Indonesia. The data analysis method in this research is descriptive statistics, characteristic data, simple validation and regression analysis with a significance level of 5%, and tested by path analysis. Data processing methods use the help of SPSS 23.0 For Windows Software. Based on the results of the analysis, it is known that the management system has a positive and significant effect on employee performance at PT. Charoen Pokphand Indonesia